Increasing Co-occurrence of Additional Autoimmune Disorders at Diabetes Type 1 Onset Among Children and Adolescents Diagnosed in Years 2010–2018—Single-Center Study - Głowińska-Olszewska, Barbara; Szabłowski, Maciej; Panas, Patrycja; Żoła̧dek, Karolina; Jamiołkowska-Sztabkowska, Milena; Milewska, Anna Justyna; Kadłubiska, Anna; Polkowska, Agnieszka; Łuczyński, Włodzimierz; Bossowski, Artur (Frontiers in Endocrinology, 2020)
OBJECTIVES: The prevalence of type 1 diabetes mellitus (T1D) in children is growing, but its relation to other autoimmune disorders that coexists since the onset of diabetes is not recognized. The objective of this study was to assess the incidence of T1D and the prevalence of autoimmune illnesses additionally coexisting since the diabetes mellitus onset in children during period of 9 years observation. METHODS: In this retrospective study the incidence rate of the TD1 was calculated as the total number of all cases that were newly diagnosed per 100 000 population people between 0-18 years of age. The selected age groups (0-4, 5-9, 10-14, 15-18 years) were examined respectively. The studied group included 493 children (264, [53.55%] boys), between 0 and 18 years old newly diagnosed with type 1 diabetes mellitus. Other autoimmune illnesses diagnoses were obtained from medical records taken from the first hospital treatment, when T1D was recognized. RESULTS: The annual standardized incidence rate of T1D increased from 19.2/100000 in year 2010 to 31.7/100000 in 2018 (1.7 fold over 9 years observation), with an increase in the incidence rate ratio (IRR) by 4% per year. In 61 (12.4%) of the studied group at least one additional autoimmune disease was diagnosed. The prevalence doubled from 10.4% in the year 2010 to 20.8% in the year 2018. Autoimmune thyroid illnesses were found in 37 children (7.5%), their incidence increased from 6.3% to almost twofold 12.5% in 2018. In 26 children (5.3%) coeliac disease was recognized, the prevalence increased from 4.2% to 9.8% in the studied period. The prevalence of additional autoimmune thyroid disease was higher in GADA positive (X2=3.4, p=0.04) patients, the oldest age group (15 -18 yrs) (X2 =7.1, p=0.06) and in girls (X2 =7.1, p=0.007). CONCLUSIONS: The standarized incidence rate of T1D in children increased 1.7-fold over the 9-year observation period and IRR increased 4% per year. Additional autoimmunity represents a significant comorbidity in patients with new-onset T1D. The number of children diagnosed with additional autoimmune diseases that accompany T1D is rapidly growing in all age groups throughout recent years.